2014
DOI: 10.1038/cdd.2014.26
|View full text |Cite
|
Sign up to set email alerts
|

G0/G1 switch gene 2 has a critical role in adipocyte differentiation

Abstract: Mouse 3T3-L1 preadipocytes differentiate into adipocytes when treated with 3-isobutyl-1-methylxanthine, dexamethasone, and insulin. Although mechanisms of adipogenesis, including transcriptional cascades, are understood, it is still unclear how clonally expanded cells eventually enter the terminal differentiation program. From gene expression profile studies, we identified G0/G1 switch gene 2 (G0s2) as a novel regulator of adipogenesis. The gene was found to be expressed at a higher level in white and brown ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…G0S2 is expressed in the lung and is abundant in adipose cells, and its expression increases during differentiation from preadipocytes to mature adipocytes. In these mature cells, G0S2 inhibits adipose triglyceride lipase and controls the size of cytoplasmic lipid droplets (11,19,20). Others have reported that the expression of G0S2 is diminished at P8 in lungs from mice bearing a compound deletion of both FGFR3 and FGFR4, which exhibit defective alveolarization (54).…”
Section: Lf Bear Markers Characteristic Of Mesenchymal Progenitorsmentioning
confidence: 97%
“…G0S2 is expressed in the lung and is abundant in adipose cells, and its expression increases during differentiation from preadipocytes to mature adipocytes. In these mature cells, G0S2 inhibits adipose triglyceride lipase and controls the size of cytoplasmic lipid droplets (11,19,20). Others have reported that the expression of G0S2 is diminished at P8 in lungs from mice bearing a compound deletion of both FGFR3 and FGFR4, which exhibit defective alveolarization (54).…”
Section: Lf Bear Markers Characteristic Of Mesenchymal Progenitorsmentioning
confidence: 97%
“…To date, no mutation in human G0S2 has been reported. Global and liver-specific G0s2 -KO mouse models were generated very recently and display decreased adipose tissue mass ( 24 , 25 ), enhanced lipolysis in adipose tissue, and a decrease in hepatic TG content ( 26 ). Global and adipose tissue-specific overexpression of G0S2 leads to increased fat mass, overall reduction in lipolytic activity, and fatty liver ( 16 , 19 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Successive studies confirmed high-level expression of G0S2 in adipose tissue of adult humans and animals including mice, pigs, bears and avian species [68, 7277]. In cultured human SGBS and mouse 3T3-L1 pre-adipocyte cell lines, both G0S2 mRNA and protein have been shown to exhibit adipogenesis-dependent expression [45, 61, 72, 75]. In humans, G0S2 mRNA expression in subcutaneous adipose tissue was found to be 7 times higher in mature adipocytes than in the cells of corresponding stroma-vascular fraction [77].…”
Section: Regulation Of G0s2 Mrna and Protein Expressionmentioning
confidence: 99%
“…Sequence analysis revealed that the G0S2 promoter region encompasses a potential PPAR-responsive element (PPRE), and Zandbergen et al subsequently provided evidence that G0S2 expression in adipogenesis is increased by PPARγ [72]. A separate study recently showed that knockdown of either PPAR γ or G0S2 resulted in apoptotic induction in 3T3-L1 cells before terminal differentiation [61]. The lack of notable defects in the adipose development of G0S2 whole-body knockout mice [5860], however, argues against a significant role of G0S2 in adipocyte differentiation in vivo .…”
Section: Regulation Of G0s2 Mrna and Protein Expressionmentioning
confidence: 99%